RF printed electronic devices using bio-sourced materials: risks and opportunities - Xavier, Pascal; Vuong, Tan-Phu (2022 IEEE Latin American Electron Devices Conference (LAEDC), 2022)
Like other sciences and technologies, electronics today faces an enormous challenge due to the scarcity of non-renewable resources and the need to decrease greenhouse gas emissions in order to reduce the climate change. In this context, the search for alternative roadmaps at all stages of the life cycle of an electronic product is a major issue. Additive processes, bio-sourced or organic materials and recyclable substrates are examples of subjects that can be explored to progressively substitute high impacts materials and methods by eco-friendly ones. At the same time, these solutions have a number of shortcomings that must be overcome in order for them to become economically and technically credible. In the domain of radio frequency devices, paper printed antennas and filters, electromagnetic energy harvesting systems, sensors and displays can be designed. This article presents an overview of what has been undertaken in this field by our team for over ten years for the design, fabrication and test of antennas. These devices were tested in several real environments for different applications such as anti-counterfeiting.